2016
DOI: 10.1007/s10006-016-0564-3
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatography determination of dexamethasone in plasma to evaluate its systemic absorption following intra-space pterygomandibular injection of twin-mix (mixture of 2 % lignocaine with 1:200,000 epinephrine and 4 mg dexamethasone): randomized control trial

Abstract: Intra-space (pterygomandibular space) administration of dexamethasone can achieve statistically similar plasma concentration of the drug as when the same dose is administered intramuscularly with demonstration of similar clinical effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The studies relevant to the use of twin-mix solution are summarized in table 1. 9,10,11, 26,27,28,29,30,31,32 Bhargava D et al first proposed clinical use of the twin mix anaesthesia for mandibular nerve block in 2013 by evaluating this anaesthetic technique and the admixture of drugs through their prospective clinical randomized double-blind study to evaluate latency & efficacy of twin-mix solution & 2% lignocaine with 1:200,000 adrenaline for the transalveolar extraction of impacted mandibular third molars. 9 Gaur S et al conducted a randomized controlled trial evaluating the altered twin mix local anaesthesia using two long acting amide local anesthetic solutions: bupivacaine & ropivacaine with/without 4 mg/ml dexamethasone solution for patients undergoing 3 rd molar surgical extraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies relevant to the use of twin-mix solution are summarized in table 1. 9,10,11, 26,27,28,29,30,31,32 Bhargava D et al first proposed clinical use of the twin mix anaesthesia for mandibular nerve block in 2013 by evaluating this anaesthetic technique and the admixture of drugs through their prospective clinical randomized double-blind study to evaluate latency & efficacy of twin-mix solution & 2% lignocaine with 1:200,000 adrenaline for the transalveolar extraction of impacted mandibular third molars. 9 Gaur S et al conducted a randomized controlled trial evaluating the altered twin mix local anaesthesia using two long acting amide local anesthetic solutions: bupivacaine & ropivacaine with/without 4 mg/ml dexamethasone solution for patients undergoing 3 rd molar surgical extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetics following intra-space pterygomandibular twin-mix injection has demonstrated that dexamethasone can attain statistically similar plasma concentration as when same dose is administered intramuscularly with comparable clinical consequence. 32 The pain associated with lidocaine infiltration is reduced when the pH of the drug is raised. 9,16 when dexamethasone is mixed with local anesthetic solution pH of resultant solution is increased from 4.5 to 6.…”
Section: Stability Of Twin MIX Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory action of dexamethasone is 20-30 times higher than cortisol, and a t1/2 of 36-54 h makes it the drug of choice as a single dose in the management of collateral effects associated with surgical removal of third molars (60,61).…”
Section: Figurementioning
confidence: 99%
“…Recently, various analytical methods have been developed for detecting DEX, such as high-performance liquid chromatography (Bhargava et al, 2016;Dési, Kovács, Palotai, & Kende, 2008;Lasić, Bobarević, & Nikolin, 1989;Tsuei, Ashley, Moore, & McBride, 1978), gas chromatography-mass spectrometry (Amendola, Garribba, & Botrè, 2003;Bagnati et al, 1996;Huetos Hidalgo, Jiménez López, Ajenjo Carazo, San Andrés Larrea, & Reuvers, 2003), liquid chromatography-mass spectrometry (LC-MS) (Chen et al, 2011;Creaser, Feely, Houghton, Seymour, & Teale, 1996), radioimmunoassay methods (Meikle, Lagerquist, & Tyler, 1973), and enzyme immunoassay (Hassan, Rowell, Hambleton, & Jackson, 1998;Vdovenko, Gribas, Vylegzhanina, & Sakharov, 2012;Yadav et al, 2013;Yoshino, Yoshiharu, Noriko, Kiyoshi, & Fukuko, 1992). Each method has its own strong and weak points.…”
Section: Introductionmentioning
confidence: 99%